Carbachol induces nitric oxide generation in guinea-pig gallbladder - (:unkn) unknown (My University, 2002)
Objective: Acetylcholine is one of the major contractile transmitters in gallbladder; whereas, it is also innervated by non-adrenergic noncholinergic nerves which mediate relaxation. It was postulated that nitric oxide (NO) which activates soluble guanylate cyclase to increase cyclic GMP (cGMP) levels in the target cells may be involved in these processes. This study was designed to investigate whether muscarinic receptor stimulation via carbachol (CCh) induces NO-mediated cGMP synthesis in guinea-pig gallbladder. Methods: cGMP levels were measured via radioimmunoassay in gallbladder slices incubated with carbachol (CCh) (10-6-10-3 mol/l) in the presence and absence of NO synthase (NOS) inhibitor L-NAME or muscarinic antagonist scopolamine. The effect of L-NAME and another NOS inhibitor L-NMMA on carbachol-induced contractions were also investigated in an in vitro organ bath. Results: Carbachol stimulated cGMP formation in guinea-pig gallbladder slices significantly. CCh-induced cGMP formation was abolished by both L-NAME (1 mmol/l) and scopolamine (10-8- 10-6 mol/l). In contraction experiments, L-NAME (3x10-4 mol/l) did not produce any change in the resting tension of the strips and the concentration-response curves to carbachol, whereas L-NMMA (3x10-4 mol/l) induced a slight, but significant contraction (6.3±1.9 % of carbachol (10-6 mol/l)-induced response). When carbachol was added to the bath after L-NMMA-induced increase in tension reached its maximum, the amplitude of the contractile response at the end was 108.0±4.0 % of the control. Conclusion: Therefore, it may be concluded that muscarinic receptor activation by carbachol stimulates NO production in guinea-pig gallbladder and the subsequent increase in cGMP counteracts with carbachol-induced contractions. However, it seems likely that an intact enteric nervous system is required for such an interaction to be prominent. The muscarinic receptor subtype(s) involved in this interaction remains to be elucidated.
Keywords: CGMP; Gallbladder; Guinea-pig; L-NAME; L-NMMA; NO